Classifying Secondary Task Driving Safety Using Method of F-ANP. (February 2015) - Jin, Lisheng; Li, Keyong; Jiang, Yuying; Xian, Huacai; Gao, Linlin
This study was designed to build an evaluation system for secondary task driving safety by using method of Fuzzy Analytic Network Process (F-ANP). Forty drivers completed driving on driving simulator while interacting with or without a secondary task. Measures of fixations, saccades, and vehicle running status were analyzed. According to five experts' opinions, a hierarchical model for secondary task driving safety evaluation was built. The hierarchical model was divided into three levels: goal, assessment dimension, and criteria. Seven indexes make up the level of criteria, and the assessment dimension includes two clusters: vehicle control risk and driver eye movement risk. By method of F-ANP, the priorities of the criteria and the subcriteria were determined. Furthermore, to rank the driving safety, an approach based on the principle of maximum membership degree was adopted. At last, a case study of secondary task driving safety evaluation by forty drivers using the proposed method was done. The results indicated that the application of the proposed method is practically feasible and adoptable for secondary task driving safety evaluation.